PENGARUH ANGKA OKTAN TERHADAP PERFORMA DAN EMISI GAS BUANG HONDA NEW MEGA PRO 150 CC - Muhammad Baitul Akbar Laduni (UNIVERSITAS ISLAM MALANG, 2022)
Selection of the wrong type of fuel oil can affect engine performance and vehicle exhaust emissions. Fuel is distinguished by the number of octane levels it has. The higher the octane number of the fuel, the better the quality of the fuel. The purpose of this experiment is to determine the effect of octane number on torque (kg.m), effective power (PS), specific fuel consumption (kg.ps-1.hour-1), carbon monoxide emissions (%) and hydrocarbon emissions (ppm). The method used is a true experimental design. The experimental results show that the highest torque at 3000-6000 rpm uses 98 octane fuel which is 59.51 kgm, 92 octane fuel is 60.57 kgm, and 90 octane fuel is 40.52 kgm.The highest effective power at 3000-6000 Rpm is obtained on 98 octane fuel, which is 318.83 PS and the smallest on 90 octane fuel, which is 182.63 PS. The best specific fuel consumption (SFC) and thermal efficiency is to use 98 octane fuel at all Rpm.The test results using the Automotive Emisson Analyzer Hg-5210 show that 90 octane fuel produces quite high carbon monoxide and hydrocarbon emissions, while 92 octane fuel is quite low, and 98 octane produces the least exhaust gas emissions. Keywords: Oktane Number, Effective Power, Torque, SFC, Thermal Efficiency, Exhaust Gas Emissions